Comunidades de práctica de la lengua caboverdiana y de A Fala de Xálima. Estudio comparativo - Natalia Czopek; Bartosz Dondelewski (Studia Linguistica)
The aim of this paper is to analyse some aspects of the sociolinguistic situation of the Cape Verdean archipelago, applying the assumptions of the community of practice theory. It is the second part of a broader comparative study juxtaposing two linguistic communities: Xálima and Cape Verdean, through the prism of the same theory. We define the community of practice as an aggregate of people who come together around mutual engagement in an endeavour of preserving and promoting their vernacular language. The empirical material will be a series of anthropological observations and comments on the semi-directed interviews, made in situ by the authors, in which we will compare, for instance, the efforts towards the orthographic standardization of the two systems and their possible effects. We aim to demonstrate that the methodological principle of community of practice is transversal, applicable and suitable to shed new light over diverse sociolinguistic minorized contexts, thus revealing otherwise poorly visible similarities.